Second order bandstop and bandpass filters using transformers. Issue 8 (August 2015) - Maundy, B.J.; Elwakil, A.S.
Abstract This paper demonstrates how transformers which have historically been used for impedance matching and/or voltage and current scaling purposes can be used to simultaneously filter signals. In particular, second order notch or bandpass filters are shown to be possible with ideal transformers. Three basic topologies are employed around a set of all possible LC resonant/non-resonant and canonical impedances and the results of the centre frequency gain, pole frequency and pole quality factor are tabulated. The non-ideal transformer is also examined. Simulations and experimental results using surface mounted transformers of area <alternatives><inline-graphic xlink:href="ark:/27927/pgj1w6r9vch" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />0.82cm2</alternatives> are provided and they confirm the expected theory.